Análise multiparamétrica da Pressão Inspiratória Nasal (SNIP) na distrofia muscular de Duchenne: um estudo de caso-controle com indivíduos saudáveis - Batista, Ilsa Priscila dos Santos (2025)
Background: Individuals with Duchenne Muscular Dystrophy (DMD) have respiratory muscles changes that lead to fatigue and weakness. Assessment of relaxation rates and contractile properties of inspiratory muscles has been described as an adjunct measure to identify early respiratory muscle fatigue in different populations. Aim: To assess the relaxation and contractile rates of inspiratory muscles non-invasively by measurement of sniff nasal inspiratory pressure (SNIP) in individuals with DMD and compare them with matched healthy subjects. Methods: Case-control study with DMD subjects and healthy controls. We assessed spirometry, maximal respiratory pressures and SNIP in all subjects. From the SNIP curve we calculated the maximum relaxation rate (MRR), the constant decay curve (τ, tau) and the maximum rate of pressure development (MRPD). Results: We studied 32 individuals with DMD and compared them with 32 age-matched and male healthy subjects (12.7 ± 5.1 years). Individuals with DMD had lower lung function and respiratory muscle strength compared to healthy subjects (p < 0.001). Also, the DMD group had a significantly lower MRR (5.9 [5.1– 6.9] vs. 8 [6.9– 10.3] %/ms, p = 0.001) and MRPD (-0.38 [-0.47 to -0.26] vs. -0,62[-0,52 to -0,80] cmH2O/ms− 1, p = 0.001), in addition a higher τ (65.7 [50.7–78.1] vs 40.5 [30.2–48.7] ms, p = 0.001). Moreover, ROC curves demonstrated that the parameters derived from the SNIP curve effectively distinguished between individuals with DMD and healthy subjects. [SNIP (AUC 0.94 p < 0.001), MRR (AUC 0.86 p < 0.001), τ (AUC 0.92 p < 0.001) and MRPD (AUC 0.89 p< 0.001)]. Conclusions: The contractile properties and relaxation rates of the inspiratory muscles are impaired in individuals with DMD, indicating an early onset of muscle weakness or fatigue. Furthermore, parameters derived from the SNIP curve can effectively differentiate between individuals with DMD and healthy subjects, aiding in the early detection of these changes in clinical practice.